Forecast-Oriented Assessment of Decadal Hindcast Skill for North Atlantic SST - Borchert, Leonard F.; Düsterhus, André; Brune, Sebastian; Müller, Wolfgang; Baehr, Johanna (Geophysical Research Letters, 2019)
International audience We demonstrate in this paper that conventional time-averaged decadal hindcast skill estimates can overestimate or underestimate the credibility of an individual decadal climate forecast. We show that hindcast skill in a long period can be higher or lower than skill in its subperiods. Instead of using time-averaged hindcast skill measures, we propose to use the physical state of the climate system at the beginning of the forecast to judge its credibility. We analyze hindcasts of North Atlantic sea surface temperature (SST) in an initialized prediction system based on the MPI-ESM-LR for the period 1901-2010. Subpolar North Atlantic Ocean heat transport (OHT) strength at hindcast initialization largely determines the skill of these hindcasts: We find high skill after anomalously strong or weak OHT, but low skill after average OHT. This knowledge can be used to constrain conventional hindcast skill estimates to improve the assessment of credibility for a decadal forecast. Plain Language Summary Credible predictions of climate up to 10 years into the future, so-called decadal climate predictions, can be a potent tool for decision makers. However, previous work indicated that such predictions are sometimes credible and sometimes not. This study illustrates that knowing the physical state of the climate system at the start of a decadal climate prediction helps assessing the credibility of that prediction. Analyzing sea surface temperature in the North Atlantic as a case study, we show that northward heat transport in the ocean provides a good indicator of the credibility of decadal predictions in the North Atlantic. Unlike previous studies, we do not only analyze time-averaged prediction credibility, but look at individual predictions in the past. This makes our findings particularly relevant for individual forecasts and decision makers.